Diet untuk Pemeliharaan Kupu-Kupu Beras, Corcyra cephalonica St. (Lepidoptera: Pyralidae) - Osman, Noorma; Nordin, Norida (1990)
The effects of five kinds of yeast (Brewer, Baker, Torula, Extract and 'ragi tapai) and five kinds of cereal grain (milled rice, corn, groundnut, mungbean and pigeon pea) were determined on the percentage adult emergence, female fresh body weight and the development period of Coreyra eephaloniea St., in order to select a suitable diet for laboratory rearing. A mixture of ground corn and milled rice (1:1) by weight, plus 5% Baher's yeast produces the highest percentage of adult emergence (98), heaviest adult females (26.37mg) and the shortest development period from larval to adult stage (32.9 days). Thus this mixture was selected as the best diet for rearing C. cephaloniea in the labomtory. Information on the following aspect of the biology of C. eephaloniea is discussed: percent Jertility and incubation period of eggs; number of larval instar and its duration; size, weight and pupal duration; and fertility, longevity and ratio of adults.